CBIO-16. SUPPRESSION OF HISTONE H3.3 MITOTIC PHOSPHORYLATION DRIVES DEVELOPMENT OF H3K27M-MUTANT DIFFUSE MIDLINE GLIOMAS. (9th November 2020) - Day, Charles; Langfald, Alyssa; Grigore, Florina; Sepaniac, Leslie; Stumpff, Jason; Vaughan, Kevin; Robinson, James; Hinchcliffe, Edward
Abstract: Pediatric midline gliomas – including DIPG – are lethal brain tumors in children, with poor prognosis and limited treatment options that provide only short-term benefits. The majority have a lysine-to-methionine substitution at residue 27 (H3K27M) in genes expressing histone H3 – predominantly in the H3.3 variant. This causes a global reduction in H3 Lys27 tri-methylation (H3K27Me3), comprehensive epigenetic reprogramming, and is a key driver in gliomagenesis. We show that the H3.3K27M mutation also induces chromosome segregation defects, which in high-grade tumors, results in extensive copy number alterations (CNAs). Ser31 is one of five amino acid substitutions differentiating H3.3 from canonical H3.1. Mitotic phosphorylation of H3.3 Ser31 by Chk1 kinase is restricted to pericentromeric heterochromatin, where it plays a role in chromosome segregation. We show that the K27M mutation affects neighboring Ser31 phosphorylation and pericentromeric heterochromatin organization. We demonstrate that (i) H3.3 K27M protein is defective for Ser31 phosphorylation by Chk1 kinase in vitro; (ii) DIPG cell lines have significantly decreased mitotic Ser31 phosphorylation, and are chromosomally unstable; and (iii) CRISPR-reversion of H3.3K27M to Lys27 restores phospho-Ser31 (and Lys27 tri-methylation) and significantly decreases chromosome instability. Expression of H3.3K27M or non-phosphorylatable H3.3S31A mutants in WT cells results in chromosome missegregation; this is suppressed by co-expression of phospho-mimetic H3.3K27M/S31E. In normal cells, chromosome missegregation stimulates p53-dependent cell cycle arrest in G1 to prevent the proliferation of aneuploid daughters. However, cells expressing H3.3 K27M or S31A failed to arrest following missegregation - despite having WT p53. Finally, in a novel mouse model of glioma, mean survival of mice with tumors induced with H3.3K27M and H3.3S31A was 81 and 68 days: 100% of H3.3S31A mice developed high-grade tumors. H3.3 WT controls developed only low-grade tumors and all survived 100 days. H3.3S31A is WT for Lys27 tri-methylation and thus, loss of Ser31 phosphorylation alone is oncogenic.